Sustainable Economic Development Indicators: The Case of Turkey - Soylemez, Ismet; Dogan, Ahmet; Ozcan, Ugur (World Scientific Publ Co Pte Ltd, 2016)
Sustainable development indicators are a good road map for financial, social and economic targets of countries. This paper aims to show which indicators are affect sustainable development of Turkey for last twelve years. 132 sustainable development indicators determined by European Union Statistical Office (Eurostat). Sustainable development indicators are calculated by related unit, institution or establishment in the direction of definitions determined by Eurostat. These indicators are calculated by TUIK (Turkish Statistical Institute) for Turkey. Some indicators as follows: socio-economic development, sustainable consumption and production, climate change and energy, sustainable transport, financing for sustainable development. However, only economic indicators are presented and analyzed in the case study. Official development assistance has tenfold rise in the last 12 years. These indicators will show which areas at economic changes should be considered to the sustainable development of country.
Soylemez, Ismet/0000-0002-8253-9389; Ozcan, Ugur/0000-0001-8283-9579;
Keywords: Sustainability Development Indicators; Economic Development; Energy Consumption; Employment Rate